Melt processable homo- and copolyimides with high thermo-oxidative stability as derived from mixed thioetherdiphthalic anhydride isomers (eXPRESS Polymer Letters, 2010)
A series of homo- and copolyimides based on mixed thioetherdiphthalic anhydride isomers (mixed-TDPA) were synthesized with several kinds of aromatic diamines. The properties of these polyimides were characterized by glass transition temperature (Tg), thermal decomposition temperature, and melt processability. A series of copolyimides were prepared to achieve high Tg concurrently with melt processability by means of selecting appropriate diamines and their composition in the copolyimides. As a result, we obtained rheological information for a series of polyimide resins as a function of temperature, time and shear rate. It is found that the processability (e.g., melt viscosity of polyimides) and ultimate product properties (e.g., Tg of polyimides) can be systematically varied by changing the variety and composition of the aromatic diamines. It has been demonstrated that the incorporation of meta- or flexible diamines improve the melt processability of polyimides significantly. Meanwhile, Tg of copolyimides from dual-diamines can be predicted and regulated. Accordingly, copolyimides from 1,3-phenylenediamine (m-PDA) and 3,4’-oxydianiline (3,4’-ODA) were obtained with higher Tg and lower melt viscosity. Such correlations of chemical structures and rheological behavior provide the necessary database for tailor-making new polyimide systems with desirable processability and physical properties.